Comprehensive approach for highly resorbed mandibular ridge with complete denture - Alfian Rahmat; Permatasari Nina; Eri Hendra Jubhari (Indonesia Prosthodontic Association, 2022)
A 66-years-old female patient was referred to Dental Hospital of Hasanuddin University with a fractured lower den-ture that impaired patient’s masticatory ability. Clinical examination showed full edentulous in both maxilla and man-dible with flat mandibular ridge, absence of inflammatory signs, flabby tissues, and bone prominences as well. The treatment plan was fabrication of complete denture with semi-adjustable articulator and modification in impression technique in order to produce retentive dentures. Preliminary impression and fabrication of anatomic cast followed by bolder molding and physiological impression. Two-dots method was used to determine the maxillomandibular re-lation and measure vertical dimension. Position of the maxilla was transferred using facebow, which attached to the centric tray followed by mounting the cast on a semi-adjustable articulator with guidance from centric tray. Artificial teeth were arranged in lingualized occlusion scheme on wax-pattern and try-in was done. After processing, remount-ing and selective grinding were performed followed by finishing and polishing, and lastly with insertion of both den-tures. It is concluded that impression technique is one of the primary factors in management of flat mandibular ridge in order to utilize surrounding tissues to have both active and passive retention in dentures.